Fabrication and Mechanical Performance of Graphene Nanoplatelet/Glass Fiber Reinforced Polymer Hybrid Composites - Yao, Xudan; Kinloch, Ian A.; Bissett, Mark A. (Frontiers in Materials, 2021)
Glass fibre reinforced polymer (GFRP) composites are promising alternatives for the traditional carbon steel pipes used in the oil and gas industry due to their corrosion and chemical resistance. However, the out-of-plane mechanical properties of GFRPs still need further improvement to achieve this goal. Hence in this work, two methods combining either vacuum mixing or spray coating with vacuum assisted resin infusion were studied to fabricate graphene nanoplatelet (GNP)/GFRP hybrid composites. The former method resulted in a severe filtering effect, where the GNPs were not evenly distributed throughout the final composite, while the latter process resulted in a uniform GNP distribution on the glass fabrics. The addition of GNPs showed no modest contribution to the tensile performance of the GFRP composites due to the relative high volume and in-plane alignment of the glass fibres. However, the GNPs did improve the flexural properties of GFRP with an optimal loading of 0.15 wt. % GNPs resulting in flexural strength and modulus increases of 6.8% and 1.6% respectively. This work indicates how GNPs can be advantageous for out-of-plane mechanical reinforcement in fibre reinforced composites.